2001
DOI: 10.1002/mrd.1041
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel gene, sperm‐tail‐associated protein (Stap), in mouse post‐meiotic testicular germ cells

Abstract: During mammalian spermatogenesis, many specific molecules show the dynamics of expression and elimination, corresponding with the morphological differentiation of germ cells. We have isolated a novel cDNA designated F77 from mouse testis by cDNA subtractive hybridization between normal and sterile mice, using the C57BL/6 congenic strain for the hybrid sterilityhyphen;3 lpar;Hsthyphen;3rpar; allele from Mus spretus. The full-length F77 mRNA was 3.4 kb and showed significant nonmatching with entries in the datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Because there are no known and characterized relatives, only very indirectly relevant information is available. Database searching on the basis of the unusually glutamate-rich amino acid composition reveals a similarity to intermediate filament proteins as well as to the sperm tail-associated proteins, Stap [26], or Spag5 [27], which is similar to the mitotic spindle protein Deepest and frog prothymosin-␣, which has a nuclear localization [28]. The analysis of secondary structure supports this by predicting long uninterrupted alpha-helical features, whose charge distribution would presuppose the formation of polymeric fibrils.…”
Section: Discussionmentioning
confidence: 83%
“…Because there are no known and characterized relatives, only very indirectly relevant information is available. Database searching on the basis of the unusually glutamate-rich amino acid composition reveals a similarity to intermediate filament proteins as well as to the sperm tail-associated proteins, Stap [26], or Spag5 [27], which is similar to the mitotic spindle protein Deepest and frog prothymosin-␣, which has a nuclear localization [28]. The analysis of secondary structure supports this by predicting long uninterrupted alpha-helical features, whose charge distribution would presuppose the formation of polymeric fibrils.…”
Section: Discussionmentioning
confidence: 83%
“…16 A previous study indicated that PMFBP1 was expressed in adult mouse testis, and more specifically, mRNA was highly expressed in round sperm and protein localized to the flagella of elongated sperm. 18 Rat Pmfbp1 (also known as ODF3 or Stap) is highly expressed in the testis of 6-to 21-week-old rats (https://www.ncbi.nlm.nih.gov/gene/171414). Our study was a combined investigation of human and mouse genetics, and based on our findings, suggests that PMFBP1 plays an important role in spermiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-exome sequence analysis of one of the brothers implicated a homozygous nonsense mutation (Table S2), c.1462C>T (p.Gln488*), in the coding region of PMFBP1 (GenBank: NM_031293.2), a gene specifically expressed in testis that encodes a sperm tail-associated protein (STAP), but its complete function had not yet been determined. 25 To determine whether PMFBP1 is another acephalic spermatozoa syndrome-related gene, similar to SUN5 that we recently reported, we Sanger sequenced PMFBP1 in ten additional infertile men with acephalic spermatozoa syndrome and without SUN5 mutations. 18 1A and 1B, Tables S1 and S2, see Supplemental Note).…”
Section: Pmfbp1 and Acephalic Spermatozoa Syndromementioning
confidence: 96%